Market Sensing Capability and Export Channel Choice: Unveiling Their Impact on Export Performance in the Indonesian Furniture Industry - Arifin, Samsul; Rifqy Roosdhani, Mohamad; Ali, Ali (PT. EQUATOR SINAR AKADEMIA, 2025)
This study investigates the relationships between market sensing ability, export channel selection, and export performance in Indonesia's furniture sector, aiming to enhance its global competitiveness. Using a quantitative approach, the research gathers secondary data from trade statistics and industry reports alongside primary data from a questionnaire survey of furniture producers, selected through stratified random sampling. The data is analyzed using partial least squares structural equation modeling (PLS-SEM). The findings indicate that market sensing capability significantly boosts export performance, with export channel choice both directly influencing performance and moderating the relationship between sensing ability and success. Firms that diversify their export channels are better positioned to leverage market insights, improving their global performance. This study contributes to the literature by exploring the combined impact of export channel selection and market sensing ability on export success, particularly within Indonesia’s furniture industry. The conclusions underscore the importance of developing strong market sensing skills and making informed export decisions to improve performance. Policymakers are encouraged to foster initiatives that enhance these capabilities, while practitioners should prioritize market intelligence and strategic export channel selection to remain competitive internationally.